The (im)possibility of communication with nonhuman beings: with digital screen printing of luminous bacteria - Saeki, Takumi; Masuda, Nobuhiro; Jo, Kazuhiro (Frontiers in Communication, 2024)
In the current media environment, John Durham Peters emphasizes the importance of non-verbal communication and notes that underpinned by digital technology, “media” is returning to its original meaning as the milieu that surrounds living beings. To concretize and critically discuss this idea, this paper examines the artworks created by the authors, which incorporate microorganisms into digital technology. These works applied luminous bacteria as ink to digitally screen print text and images. The first work, A Medium for Images or Luminous Bacteria (2022), prints Japanese text with luminous bacteria ink. The second work, ‘イ(I)’ (1926) by BioLuminescent Bacteria (2024), recreates the first image in the history of Japanese television, ‘イ(I)’, with luminous bacteria. This paper compares and analyzes these practices in light of classical media theory, including the work of William Ivins Jr. and Marshall McLuhan. The paper introduces another work, Grow.|Glow. (2023), to further expand the discussion to contemporary digital media. Finally, drawing on the recent arguments of Anna Tsing and Antonio Damasio, we elucidate the critical implications that the works of luminous bacteria bring to the current media environment.